2017
DOI: 10.1016/j.bios.2016.08.097
|View full text |Cite
|
Sign up to set email alerts
|

The capacitive sensing of NS1 Flavivirus biomarker

Abstract: NS1 is a biomarker for different Flavivirus diseases such as dengue (DENV), zika (ZIKV) and chikungunya (CHIKV) and was herein selectively quantified by electrochemical capacitive sensing (an impedance-derived capacitance methodology wherein the redox probe is contained in the receptive layer) mainly aiming dengue diagnosis in phosphate buffer saline and blood serum environments (up to the neat level). The capacitive sensing was compared to traditional concurrent impedimetric approach (in which the redox probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 62 publications
1
47
0
Order By: Relevance
“…This corresponded to observed increases in immunoagglutination with increasing ZIKV concentration, despite the complexity of the serum matrix. This detection limit is equivalent to that observed in a plasmonic resonance‐based immunosensor, and exceeds those observed by capacitive and impedimetry‐based immunoassays (LOD=0.5–30 ng/mL in serum) . In addition, our assay time is much reduced (30 s) from those described above …”
Section: Figurementioning
confidence: 59%
See 2 more Smart Citations
“…This corresponded to observed increases in immunoagglutination with increasing ZIKV concentration, despite the complexity of the serum matrix. This detection limit is equivalent to that observed in a plasmonic resonance‐based immunosensor, and exceeds those observed by capacitive and impedimetry‐based immunoassays (LOD=0.5–30 ng/mL in serum) . In addition, our assay time is much reduced (30 s) from those described above …”
Section: Figurementioning
confidence: 59%
“…This detection limit is equivalent to that observed in ap lasmonic resonancebased immunosensor, and exceeds those observed by capacitive and impedimetry-based immunoassays (LOD = 0.5-30 ng/ mL in serum). [28,29] In addition, our assay time is much reduced (30 s) from those described above. [28,29] In conclusion, this novel capillary flow-based transducer mechanism shows promise for applicationsi nf ield-deployable diagnostics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent immunosensors developed and tested by Cecchetto et al, for example, use impedimetric and capacitive sensing of the NS1 protein from DENV, and have the potential for near immediate conversion to ZIKV detection due to potential cross-reactivity of the anti-NS1 IgG1 antibodies employed [61] (Table 2). Similarly, flavivirus biosensors have been developed using lab-on-a-chip and lab-on-a-CD technology for label-free optical and electrochemical sensing of DENV through serological IgM or NS1 protein binding [62, 63].…”
Section: Developmental Diagnostic Methodsmentioning
confidence: 99%
“…To date a number of low cost diagnostic platforms for NS1 have been reported, including those based on impedimetric analyses (Parkash and Shueb, 2015;Teles, 2011;Wong et al, 2016;Tai et al, 2006;Su et al, 2003;Oliveira et al, 2009;Cecchetto et al, 2015Cecchetto et al, , 2017Darwish et al, 2016). For example, Cecchetto et al (2015) have reported an impedimetric biosensor to detect NS1 both in PBS and serum using a surface tethered anti-NS1 antibody.…”
Section: Introductionmentioning
confidence: 99%